A Sustainable Urban Sprawl?: The Environmental Values of Suburban Interstitial Spaces of Santiago de Chile. Issue 3 (3rd July 2021) - Silva, Cristian; Ma, Jing
Abstract: Urban sprawl in Latin America is described as one of the major problems of 'the growth machine'. As a reaction, most planning policies are based on anti-sprawl narratives, while in practice, urban sprawl has been thoroughly consolidated by all tiers of government. In this paper – and using the capital city of Chile, Santiago, as a case study – we challenge these anti-sprawl politics in light of the emerging environmental values and associated meanings of the interstitial spaces resulting from land fragmentation in contexts of urban sprawl. Looking at the interstitial spaces that lie between developments becomes relevant in understanding urban sprawl, considering that significant attention has been paid to the impact of the built-up space that defines the urban character of cities and their governance arrangements. We propose that looking at Santiago's urban sprawl from the interstitial spaces may contribute to the creation of more sustainable sprawling landscapes and inspire modernisations beyond anti-sprawl policies. Finally, it is suggested that a more sustainable urban development of city regions might include the environmental values of suburban interstices and consider them as assets for the creation of more comprehensive planning and policy responses to urban sprawl.